THE ESSENCE, CLASSIFICATION, AND OPERATIONAL MECHANISMS OF ISLAMIC FINANCE INSTRUMENTS (American Journal of Business Management, Economics and Banking, 2025)
This article presents an in-depth academic exploration of the essence, systematic classification, and functional mechanisms of Islamic finance instruments within the framework of contemporary financial systems. Through a qualitative approach, the paper discusses the theoretical underpinnings and practical implementation of Shariah-compliant financial contracts such as Mudarabah, Musharakah, Murabaha, Ijarah, and Sukuk. It evaluates their role in promoting ethical, asset-based, and risk-sharing finance in both Muslim-majority and non-Muslim jurisdictions. The study underscores the significance of Islamic financial instruments in contributing to financial inclusion, economic justice, and sustainable development, while also identifying key challenges in standardization, regulation, and awareness that must be addressed to realize the full potential of Islamic finance globally.